Pengaruh Nilai Carbon Equivalen (CE) Dari Cast Iron Pada Proses Penangkaian Anoda Di Rodding Plant - Dede Ibrahim Muthawali (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Addition of the substance will effect the value of carbon equivalent (CE) cast iron. Carbon equivalent value is a parameter that tells us how much carbon is cointained in the cast iron. Carbon equivalent values were determined between 4,7 to 4,9. When the carbon equivalent (CE) on the cast iron is less than 4.7 to 4.9 then it will be easy to cast iron, causing cracks in the baked anode rod will come loose. And usage cast iron is not optimal. And when more than that value so cast iron will difficult loose from the anode rod. From the observations that have been made obtainable carbon equivalent (CE) cast iron are 3,76 and 4,7. This indicates that the value of carbon equivalent (CE) cast iron still eligible and meet the standars that have been established which is between 4,7 to 4,9.